Let love rule - Kravitz, Lenny; Ritz, David (Henry Holt and Company, 2020)
Kravitz looks back at his life with candor, self-scrutiny, and humor. It's the story of a wildly creative kid who, despite tough struggles at school and extreme tension at home, finds salvation in music. Readers will follow his growth as a musician and ultimately a master songwriter, producer, and performer. Kravitz also discusses his spiritual growth, and the powerful way in which spirit informs his music. -- adapted from jacket